Moral Value in Ludruk “Ande-Ande Lumut” for Yosowilangun Community, Lumajang District: Pendahuluan, Metode, Hasil dan Pembahasan, Simpulan, daftar Pustaka. - Pratiwi, Reni Dwi; Sunu Catur Budiyono (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This research aims to describe the moral values of ludruk “Ande-Ande Lumut” for the people of Yosowilangun, Lumajang Regency. Ludruk is a perfoming art that aims to entertain the audience, this art is proof of the richness of Indonesia culture and traditional arts. There are two formulations of the problem in this research, namely 1) what are the moral values contained in the ludruk “Ande-Ande Lumut” for the people of Yosowilangun, Lumajang Regency? And 2) what is the meaning of the story “Ande-Ande Lumut” for the people of Yosowilangun, Lumajang Regency? The moral values in the ludruk “Ande-Ande Lumut” are very interesting to study using leterary anthropology theory because it analyzes literature from a cultural aspect. The approach used is a qualitative a approach with descriptive methods. The data source in this research is a video of the ludruk perfomance “Ande-Ande Lumut”. Data collection tecniques in this research are observation, interviews, and documentation. The data analysis technique uses three stages, namely data reduction, data presentation, dan drawing conclusions. The result of this research show that there is a moral value from the quotes or conversations contained in the ludruk “Ande-Ande Lumut” as follows; mutual help, kindness, honesty, human relations with religion or belief, and responsibility.